Associations of lockdown stringency and duration with Google searches for mental health terms during the COVID-19 pandemic: A nine-country study. (June 2022) - de la Rosa, Pedro A.; Cowden, Richard G.; de Filippis, Renato; Jerotic, Stefan; Nahidi, Mahsa; Ori, Dorottya; Orsolini, Laura; Nagendrappa, Sachin; Pinto da Costa, Mariana; Ransing, Ramdas; Saeed, Fahimeh; Shoib, Sheikh; et al.
Abstract: Objectives: We examined the associations of lockdown stringency and duration with Google searches for four mental health concepts (i.e., "Anxiety, " "Depression, " "Suicide, " "Mental Health") in nine countries (i.e., Hungary, India, Iran, Italy, Paraguay, Serbia, South Africa, Spain, Turkey) during the COVID-19 pandemic. Methods: We retrieved national-level data for each country from Google Trends and the Global Panel Database of Pandemic Policies. In our primary analysis, we used data from all countries to estimate a set of multilevel regression models examining associations of overall lockdown stringency and lockdown duration with relative search volumes for each mental health term. We repeated the models after replacing overall lockdown stringency with each of the lockdown stringency components. Results: A negative association was found between overall lockdown stringency and "Depression." Lockdown duration and the most stringent stay-at-home requirements were negatively associated with "Anxiety." Policies that recommended or required the cancelation of public events evidenced negative associations with "Depression, " whereas associations between policies that required some or all levels of schooling to close and "Depression" were positive. Policies that recommended or required workplaces to close and those that enforced quarantines on non-citizens arriving from high-risk regions or closed borders entirely were negatively associated with "Suicide." Conclusions: Lockdown duration and some lockdown policies during the COVID-19 pandemic were generally associated with significantly lower, rather than higher, Google searches for selected mental health terms. These findings could be used alongside other evidence to develop future lockdown strategies that are sensitive to mental health issues during public health crises.